Non-Invasive Determination of Wall Structure and Material Using Synthetic Aperture Radar - Elgy, James (Cranfield University, 2018)
3MT presented at the 2018 Defence and Security Doctoral Symposium.Through-Wall remote sensing has become an area of great interest in both civilian and military sectors, with uses ranging from search and rescue to the assessment of the insulation used in building construction. Low frequency Synthetic Aperture Radar (SAR) is an attractive option due to its long-range, all-weather and non-destructive nature, with different radar modalities each providing useful information. Unfortunately, in a through-wall scenario, radar accuracy is inherently decreased due to the electrical properties of the wall material, leading to defocused and distorted images. Funded in part by Dstl, this research focuses on the remote determination of the thickness and refractive index of walls, through the use of different radar measuring geometries. In addition to providing useful auxiliary information, the knowledge of the wall properties can be used to improve the quality of through-wall SAR imagery and to address some of the fundamental limitations of the technology .
Keywords: 'Through-wall-radar'; 'Multistatic'; 'Synthetic Aperture Radar'; 'DSDS18 3MT'; 'DSDS18'; 'Image Processing'; 'Signal Processing'